Modulating Metabolic and Cardiovascular Adverse Effects of Olanzapine with Theobroma cocoa a Preclinical Insight into Synergistic Cardioprotection - Patole, Varsha Aniket; Dighe, Santosh Bhausaheb; Khemnar, Sapna Baban; damare, Gaurao subhash; bhone, Vaibhav vitthal; Jadhav, Shweta Shantaram (International Journal of Pharmaceutical Investigation, 2026)
Background Olanzapine, a widely prescribed atypical antipsychotic, is associated with significant cardiometabolic side effects, including hypertension, dyslipidaemia, oxidative stress, inflammation, and QT interval prolongation. Natural substances possessing antioxidant and anti-inflammatory characteristics, like Theobroma cocoa which is abundant in polyphenols, could provide a promising therapeutic approach to alleviate these negative effects. Objectives To investigate the cardiovascular and metabolic impact of Olanzapine, cocoa, and their combination in a controlled experimental model, focusing on blood pressure, lipid profile, inflammatory and oxidative stress markers, weight gain, and QT interval alterations. Materials and Methods Male Wistar rats were categorized into control, Olanzapine (5 mg/kg/day), OLZ+TCE (50 mg/kg/day), OLZ+TCE (100 mg/kg/day), OLZ+TCE (200 mg/kg/day) and combination groups for an 8-week treatment period. Systolic blood pressure was evaluated via the tail-cuff method. Serum concentration of LDL, HDL, triglycerides, C-reactive protein (CRP) and malondialdehyde (MDA) were analyzed. Body weight and electrocardiographic QT interval were also assessed. Data were subjected to analysis using one-way ANOVA followed by Tukey’s post hoc test (p < 0.05). Results Olanzapine substantial increased systolic blood pressure, LDL, triglycerides, CRP, MDA levels, QT interval, and body weight, while reducing HDL cholesterol (p < 0.05 to p < 0.001 vs. control). TCE+OLZ (100,200 mg/kg+5mg/kg) demonstrated cardio protective properties by enhancing all assessed parameters. Co-administration of cocoa with Olanzapine attenuated most Olanzapine-induced changes, though QT interval prolongation was not significantly reversed. Conclusion Theobroma cocoa demonstrates potential in mitigating several cardio metabolic side effects of Olanzapine in a preclinical model. These findings support further exploration of cocoa polyphenols as adjunctive agents in antipsychotic therapy to enhance cardiovascular safety.
Keywords: Olanzapine; Cocoa; Cardiovascular; Oxidative Stress; CRP; Lipid Profile; QT Interval; Metabolic Syndrome.